Investigação da hipótese de sobrerreação e sub-reação com o sentimento do investidor - Malanski, Leonardo Köppe (Revista de Negócios, 2023)
This paper aims to analyze the hypothesis of overreaction and under-reaction over the profitability of the Brazilian stock market. The theoretical review was based on the Market Efficiency and Behavioral Finance Hypothesis. Economática SA’s database was used, from where it was collected information about 1,283 stocks (571 active and 712 canceled) between January 1999 to December 2017, representing a sample of 228 months. It was applied the methodology developed by DeBondt and Thaler (1985) and Jegadeesh and Titman (1993), where portfolios composed of the upper and lower quintiles were created, based on the ranking of past stock returns. Through the means comparison test, it was possible to verify evidence that there is a phenomenon of overreaction for events of negative character after 6, 12 or 18 months of holding. However, no abnormal return was observed for overreaction of positive character events, nor any sub-reaction phenomena. Regarding investor sentiment, the results show that there is a relationship between it and the return of some strategies based on past return, contrary to Efficiency Market Hypothesis in its weak form.